(untitled) (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Cytotoxic agent is a substance that kills cells, including cancer cells, which may stop cancer cells from dividing and growing and may cause tumors to shrink in size. These may have carcinogenic, mutagenic or teratogenic effects. Nurses are directly exposed to it while handling cytotoxic agents. Objective of the study was to find out the level of knowledge regarding health hazards of cytotoxic agent among nurses working in B.P. Koirala Memorial Cancer Hospital, Bharatpur Chitwan. Method: A descriptive cross sectional study was conducted using non probability purposive sampling technique to collect the information among 106 nurses. Self-administered structured questionnaire was used to collect data. Data were analyzed by using SPSS version 22 and descriptive and inferential statistics were used. Result: The finding of the study showed that the majority of respondents (48.10%) had <2 years of work experience and educational level was Bachelor’s degree in nursing (74.50%). Only 12.30% had special course or training on health hazards of cytotoxic agent. The majority of the respondents (98.10%) had good level of knowledge regarding exposure of cytotoxic agents and 75.50% had good level of knowledge regarding hazardous effects of cytotoxic agents. The overall level of knowledge regarding health hazards of cytotoxic agents was good (88.70%). Conclusion: This study finding concluded that, nurses working at B.P. Koirala Memorial Cancer Hospital had good level of knowledge regarding health hazards of cytotoxic agents. However, in-service education and training is required.